1988
DOI: 10.1007/bf01025413
|View full text |Cite
|
Sign up to set email alerts
|

Protein reactions with methyl and ethyl vinyl sulfones

Abstract: Disulfide bonds of bovine serum albumin and wool were reduced by n-tributylphosphine to sulfhydryl groups that were then modified by methyl or ethyl vinyl sulfone in a nucleophilic addition reaction to S-(beta-ethylsulfonylmethyl)-L-cysteine and S(beta-ethylsulfonylethyl)-L-cysteine, respectively. The reductive alkylation was carried out either simultaneously, with both the reducing and alkylating agents present in the reaction mixture, or sequentially, with the reduced proteins first isolated before alkylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 7 publications
1
70
0
Order By: Relevance
“…In this context, the excellent capability of vinyl sulfones to act as Michael acceptors has been used but not fully exploited up to the present for protein modification, despiste attractive characteristics offered by this methodology such as water stability of the sulfur function for extended periods, particulary at neutral pH where they are resistant to hydrolysis, the lack of by-products in conjugated reactions, the needless use of organometallic catalysts, and the stability of the linkages formed. It is generally accepted that i) the larger nucleophilic character of thiol makes cysteine residues the preferential target of vinyl sulfone derivatized reagents, ii) the -amino groups of lysine and to a lesser extent the imidazole ring of histidine side chain are secondary targets and iii) the pH of the reaction medium may be use to control the relative reactivity of these funtional group (Friedman & Finley, 1975;Masri & Friedman, 1988). Studies on the reactivity of poly(ethylene glycol) vinyl sulfone toward reduced ribonuclease (Morpurgo et al, 1996) found that the reaction with cysteine groups is rapid and selective at pH 7-9 and with lysines proceeds slowly at pH 9.3.…”
Section: Vinyl Sulfones and Other Methodologies For Chemical Modificamentioning
confidence: 99%
“…In this context, the excellent capability of vinyl sulfones to act as Michael acceptors has been used but not fully exploited up to the present for protein modification, despiste attractive characteristics offered by this methodology such as water stability of the sulfur function for extended periods, particulary at neutral pH where they are resistant to hydrolysis, the lack of by-products in conjugated reactions, the needless use of organometallic catalysts, and the stability of the linkages formed. It is generally accepted that i) the larger nucleophilic character of thiol makes cysteine residues the preferential target of vinyl sulfone derivatized reagents, ii) the -amino groups of lysine and to a lesser extent the imidazole ring of histidine side chain are secondary targets and iii) the pH of the reaction medium may be use to control the relative reactivity of these funtional group (Friedman & Finley, 1975;Masri & Friedman, 1988). Studies on the reactivity of poly(ethylene glycol) vinyl sulfone toward reduced ribonuclease (Morpurgo et al, 1996) found that the reaction with cysteine groups is rapid and selective at pH 7-9 and with lysines proceeds slowly at pH 9.3.…”
Section: Vinyl Sulfones and Other Methodologies For Chemical Modificamentioning
confidence: 99%
“…The Vinyl Sulfone Group of Bay 11-7082 Is Required for Inhibition of the NLRP3 Inflammasome-On the basis of reports of covalent modification of proteins and nucleic acids with vinyl sulfones and acrylonitriles (25)(26)(27), we hypothesized that the trans-vinyl sulfone nitrile functional group in Bay 11-7082 might irreversibly inhibit activation of the NLRP3 inflammasome via alkylation of one or more nucleophilic residues. To assess whether alkylation is important for inhibitory activity, we first preincubated Bay 11-7082 with free glutathione or L-cysteine and then tested the ability of both pretreated and untreated Bay 11-7082 to inhibit caspase activation.…”
Section: Bay 11-7082 Is a Selective Inhibitor Of The Nlrp3 Inflammasomentioning
confidence: 99%
“…Commonly used heterocross-linkers are, for example, 1-ethyl-3-(3-(dimethylamino)-propyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS), which utilize the primary amine (−NH 2 ) groups of the amino acid side chains (Lys) of protein molecules for crosslinking 5 on a carboxyl (−COOH) modified surface. Other cross-linking strategies using −SH (cysteine), 6 −COOH (Asp, Glu), 7 and −OH (Ser, Thr) side groups of amino acids have also been investigated widely to conjugate on maleimide, amine, and epoxy 8 modified surfaces, respectively. Directional covalent immobilization of antibodies has been reported via the carbohydrate moiety in the antibody Fc region; however, this requires prior modification and purification of antibody molecules.…”
mentioning
confidence: 99%